Plain tobacco packaging: progress, challenges, learning and opportunities. Issue 2 (3rd March 2022) - Moodie, Crawford; Hoek, Janet; Hammond, David; Gallopel-Morvan, Karine; Sendoya, Diego; Rosen, Laura; Mucan Özcan, Burcu; van der Eijk, Yvette
Abstract : The aim of this paper is to overview progress made with respect to the adoption of plain (or standardised) packaging, key challenges faced, evaluative evidence and opportunities for extending this policy. It has been a decade since Australia became the first country to require tobacco products to be sold in plain packaging; after slow initial uptake, 16 countries have now fully implemented this policy. Since 2020, plain packaging laws have become more comprehensive in some countries, expanding coverage beyond traditional tobacco products to include heated tobacco, tobacco accessories (rolling papers) and other nicotine-containing products (e-cigarettes). Laws have also become more innovative: some now ban non-biodegradable filters, include provision for a periodic change of the pack colour or require both plain packaging and health-promoting pack inserts. The tobacco industry has and will continue to use multi-jurisdictional strategies to oppose this policy. Evaluations suggest that plain packaging has improved health outcomes and has not burdened retailers, although research is limited to early policy adopters and important gaps in the literature remain. While the power of packaging as a sales tool has diminished in markets with plain packaging, tobacco companies have exploited loopholes to continue to promote their products and have increasingly focused on filter innovations. Opportunities exist for governments to strengthen plain packaging laws.